METABOLIC REGULATION AND EPIGENETIC CONTROL: UNRAVELING THE COMPLEXITY OF SKELETAL STEM CELL FATE AND BONE HEALTH - Wahyuni, Afrinda Dwi (Stem Cell Research and Development Center, Universitas Airlangga, 2024)
Skeletal stem cells (SSCs) are essential for bone formation and tissue regeneration within the skeletal system. These self-regenerating cells differentiate into various skeletal cell types, maintaining skeletal health. However, aging diminishes SSC capacity, impacting skeletal integrity. Epigenetics, the study of heritable changes in gene expression, plays a crucial role in stem cell regulation. Mechanisms like DNA methylation and histone modifications control gene expression without altering the DNA sequence. Dysregulation of epigenetic processes in transplanted cells may lead to immunological rejection or functional impairment. Understanding epigenetic regulation in stem cells is vital for tissue regeneration strategies. This narrative review focuses on summarizing existing scientific literature on epigenetic regulation within stem cells, particularly skeletal stem cells. The study utilized Google Scholar to search for relevant articles using keywords like